Original paperPercutaneous mitral commissurotomy in pregnant women – long-term observations - Dąbrowski, Maciej; Chmielak, Zbigniew; Dąbrowski, Marek; Rużyłło, Witold (Advances in Interventional Cardiology/Postępy w Kardiologii Interwencyjnej, 2011)
Background : Percutaneous mitral commissurotomy (PMC) can be safely performed during pregnancy. However, there is still little known about follow-up results after PMC in populations of pregnant women taking into consideration childhood development. Aim : To evaluate long-term clinical follow-up and echocardiographic data on pregnant patients who underwent PMC in our centre and development of their infants. Material and methods : From January 1989 to December 1998, 15 pregnant women with mitral stenosis and severe congestive heart failure (mean gestational duration, 31.5 ±2.7 week) underwent PMC. The procedure was successful in all patients, resulting in a significant increase (0.85 ±0.3 cm 2 ) in mitral valve area from 1.01 ±0.24 cm 2 to 2.01 ±0.33 cm 2 (p < 0.001) and New York Heart Association (NYHA) improvement to class I or II (13 and 2 patients respectively). Results : There was no maternal death, no abortion, no intrauterine growth restriction, and no stillbirth. One baby (6.6%) had cerebral palsy at birth. Long term follow-up of 17 years and 9 months was completed for 12 patients. Two patients (13%) underwent re-PMC, and one (6.6%) surgical mitral valve replacement 15, 17 and 19 years after the first procedure, respectively. All babies maintained normal growth and development without any clinical abnormalities, thyroid disease or malignancy. Conclusion : PMC is a safe and effective procedure, with favourable long-term results in the population of pregnant women with rheumatic mitral stenosis and severe congestive heart failure.